Increasing Student Activeness Using the TaRL Approach Through Differentiated Learning on Statistics Material - Simanjuntak, Lomak Norita; Yantoro, Yantoro; Radmika, Habibah Anna; Basyir, Basyir (AlphaMath : Journal of Mathematics Education, 2024)
The aim of this research is to examine student activity. This research uses Classroom Action Research (PTK). The subjects and location of this research were class VB students at SDN 42 Jambi City, totaling 24 students. The research model used is research which includes four stages of action, namely planning, action, observation and reflection. The data analysis technique used is quantitative descriptive. The research results showed that students experienced significant improvement during the two cycles using each completeness percentage. In the pre-cycle, students' completeness was 40%. In cycle I the completeness obtained was 53% and in cycle II it reached 77% completeness or an increase of 37%. With a pre-cycle average of 40% to 53% in cycle I and increasing in cycle II to 77%. So, it can be concluded that the TaRL approach can increase student activity in teaching and learning activities in the VB class at SDN 42 Jambi City. So, it can be recommended to use the TaRL learning approach to increase student activity.